Clinical management and impact of scarlet fever in the modern era: findings from a cross-sectional study of cases in London, 2018–2019. Issue 12 (24th December 2021) - Herdman, Michael Trent; Cordery, Rebecca; Karo, Basel; Purba, Amrit Kaur; Begum, Lipi; Lamagni, Theresa; Kee, Chuin; Balasegaram, Sooria; Sriskandan, Shiranee
Abstract : Objectives: In response to increasing incidence of scarlet fever and wider outbreaks of group A streptococcal infections in London, we aimed to characterise the epidemiology, symptoms, management and consequences of scarlet fever, and to identify factors associated with delayed diagnosis. Design and setting: Cross-sectional community-based study of children with scarlet fever notified to London's three Health Protection Teams, 2018–2019. Participants: From 2575 directly invited notified cases plus invitations via parental networks at 410 schools/nurseries with notified outbreaks of confirmed/probable scarlet fever, we received 477 responses (19% of those directly invited), of which 412 met the case definition. Median age was 4 years (range <1 to 16), 48% were female, and 70% were of white ethnicity. Outcome measures: Preplanned measures included quantitative description of case demographics, symptoms, care-seeking, and clinical, social, and economic impact on cases and households. After survey completion, secondary analyses of factors associated with delayed diagnosis (by logistic regression) and consequences of delayed diagnosis (by Cox's regression), and qualitative analysis of free text comments were added. Results: Rash was reported for 89% of cases, but followed onset of other symptoms for 71%, with a median 1-day delay. Pattern of onset varied with age: sore throat was more common at onset among children 5 years and older (OR3.1, 95% CI 1.9 to 5.0). At first consultation, for 28%, scarlet fever was not considered: in these cases, symptoms were frequently attributed to viral infection (60%, 64/106). Delay in diagnosis beyond first consultation occurred more frequently among children aged 5+ who presented with sore throat (OR 2.8 vs 5+without sore throat; 95% CI 1.3 to 5.8). Cases with delayed diagnosis took, on average, 1 day longer to return to baseline activities. Conclusions: Scarlet fever may be initially overlooked, especially among older children presenting with sore throat. Raising awareness among carers and practitioners may aid identification and timely treatment.